Investigation of water hammer effect through pipeline system - Tan, Wee Choon; Prakash, Churia; Lim, Eng Aik; Teoh, Thean Hin (Indonesian Society for Knowledge and Human Development (INSIGHT), 2013)
Link to publisher's homepage at http://insightsociety.org/